The Principle of Personality as a Basis for Legal Determination in International Agreements - Mahardika, Muhammad Panji; Hamimulloh, Muhammad; Widiadnyani, I Gusti Ayu (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
This research discusses the role of the principle of personality in determining the applicable law in international agreements amidst the complexities of legal relationships resulting from globalization. The principle of personality, which emphasizes the connection of legal subjects to their state based on nationality or domicile, is proposed as a principle to provide legal certainty and justice. This study employs a normative and comparative approach to analyze the application of this principle in various international legal instruments and to evaluate its advantages and limitations. While the principle of personality offers legal certainty and protection for individuals, challenges such as jurisdictional conflicts and legal uncertainties in the context of modern business agreements are also identified. Therefore, this research aims to provide recommendations for the formulation of more adaptive and inclusive international agreements, as well as to emphasize the importance of a personal approach in creating a legal system that is responsive to global dynamics.